Comparative Efficacy and Safety of Sildenafil, Tadalafil, Vardenafil, Mirodenafil, Coenzyme Q, and Testosterone in the Treatment of Male Sexual Dysfunction: A Systematic Review and Meta-Analysis - Gaurav Uppal; Ashok Shenoy; S Sayan; Betsy Marina Babu; Asha Devi Dhandapani (BJPsych Open)
Aims: This study through systematic review approaches and meta-analysis aimed to determine safe drug options for treating male sexual dysfunction due to erectile dysfunction by comparing sildenafil, tadalafil, vardenafil, mirodenafil, coenzyme Q and testosterone.